Узагальнена модель негомогенного пуассонівського процесу для оцінювання надійності програмного забезпечення - Тимошенко, Ю.О.; Дідковська, М.В. (Інститут програмних систем НАН України, 2004)
This article is devoted to the reliability estimation’s theory and non homogeneous Poisson process models investigation. The generalized finite non Homogeneous Poisson model is proposed.